MdERF1B–MdMYC2 module integrates ethylene and jasmonic acid to regulate the biosynthesis of anthocyanin in apple. Issue 1 (23rd June 2022) - Wang, Shuo; Li, Li-Xian; Fang, Yue; Li, Dan; Mao, Zuolin; Zhu, Zihao; Chen, Xue-Sen; Feng, Shou-Qian
Abstract: Ethylene and jasmonic acid (JA) are crucial hormones that promote anthocyanin synthesis in apple ( Malus × domestica ) . However, the mechanism by which these hormones cooperate to modulate anthocyanin production in apple is unclear. According to our results, MdERF1B expression was strongly induced by ethylene and JA. Physiological phenotypes and the results of molecular biological analyses indicated that MdERF1B encodes a positive regulator of anthocyanin synthesis. Specifically, MdERF1B was capable of combining directly with the MdMYC2 promoter to promote gene expression. Additionally, MdERF1B interacted with two JA signaling pathway inhibitors, namely MdJAZ5 and MdJAZ10. The MdERF1B–MdJAZ5/10 protein complex decreased the ability of MdERF1B to activate the MdMYC2 promoter. Furthermore, MdEIL1, which is a crucial protein for ethylene signal transduction, was observed to bind directly to the MdERF1B promoter, thereby upregulating gene expression. These results suggest that MdERF1B is a core gene responsive to JA and ethylene signals. The encoded protein, together with MdMYC2, MdJAZ5/10, and MdEIL1, modulates anthocyanin synthesis in apple. This study clarifies the synergistic mechanism by which JA and ethylene regulate anthocyanin production in apple.